The effect of client-auditor mismatches on earnings management using classification shifting: Evidence from China - Shanmei Luo; Danning Yu; Shudan Jin (PLoS ONE, 2026)
Using a sample of Shanghai and Shenzhen A-share listed companies from 2008 to 2022, this study examines the impact of client-auditor mismatch on earnings management using classification shifting. The results indicate that upward mismatches—where clients engage higher-tier auditors than expected—mitigate classification shifting, while downward mismatches amplify it. Further analysis reveals that strong internal control moderates this relationship, constraining earnings management behavior. Additionally, we find that auditor industry expertise partially mediates the relationship between client-auditor mismatch and classification shifting.